no 182:
radicequadrata[(6/5 x 2/3 + 1/4 - 1/4 x 3/5) - 13/50] =
= radicequadrata[(4/5 + 1/4 - 3/20) - 13/50]; {mcm(5; 4; 20) = 20}.
= radicequadrata[(16/20 + 5/20 - 3/20) - 13/50] =
= radicequadrata[18/20 - 13/50] ; { 18/20 = 9/10}.
= radice[9/10 - 13/50] = radice[45 /50 - 13/50] =
= radice[32/50] = (32/50 si semplifica per 2);
radice[16/25] = 4/5.
@sarannn ciao
182)
$\small \sqrt{\left(\dfrac{6}{5} : \dfrac{3}{2}+\dfrac{1}{4}-\dfrac{1}{4}·\dfrac{3}{5}\right)-\dfrac{13}{50}}= $
$\small =\sqrt{\left(\dfrac{\cancel6^2}{5}·\dfrac{2}{\cancel3_1}+\dfrac{1}{4}-\dfrac{3}{20}\right)-\dfrac{13}{50}}= $
$\small =\sqrt{\left(\dfrac{2}{5}·\dfrac{2}{1}+\dfrac{1}{4}-\dfrac{3}{20}\right)-\dfrac{13}{50}}= $
$\small =\sqrt{\left(\dfrac{4}{5}+\dfrac{1}{4}-\dfrac{3}{20}\right)-\dfrac{13}{50}}= $
$\small =\sqrt{\left(\dfrac{16+5-3}{20}\right)-\dfrac{13}{50}}= $
$\small =\sqrt{\dfrac{\cancel{18}^9}{\cancel{20}_{10}}-\dfrac{13}{50}}= $
$\small =\sqrt{\dfrac{9}{10}-\dfrac{13}{50}}= $
$\small =\sqrt{\dfrac{45-13}{50}}= $
$\small =\sqrt{\dfrac{\cancel{32}^{16}}{\cancel{50}_{25}}}= $
$\small =\sqrt{\dfrac{16}{25}}= \dfrac{4}{5}$